Ablation of LAT2 Transporter Causes Intramuscular Glutamine Accumulation and Inhibition of Fasting‐Induced Proteolysis - Meritxell Espino‐Guarch; Susie Shih Yin Huang; Clara Vilches; Esther Prat; Rana El Nahas; Ghalia Missous; Susanna Bodoy; Abbirami Sathappan; Mohammad Ameen Al‐Aghbar; Clara Mayayo; Montse Olivé; Silvia Busquets‐Rius; et al. (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background The neutral amino acid transporter SLC7A8 (LAT2) has been described as a key regulator of metabolic adaptation. LAT2 mutations in human populations have been linked to the early onset of age‐related hearing loss and cataract growth. As LAT2 was previously found to be highly expressed in skeletal muscle, here we characterised its role in the regulation of skeletal muscle amino acid flux and metabolic adaptation to fasting. Methods Wild‐type (WT) and LAT2 knock‐out (LAT2KO) mice were exposed to short‐ and long‐periods of fasting (16 and 48 h). The impact of the absence of LAT2 on amino acid content, gene expression, proteolysis activity, muscle tone, and histology was measured. To characterise the impact on muscle degradation, we tested LAT2 KO mice in cancer‐associated cachexia, streptozocin‐induced Type‐1 diabetes, and ageing models. Results LAT2KO mice experienced a notable reduction in body weight during fasting (WT:14% and LAT2KO:18%, p = 0.02), with a greater reduction in fat mass (0.5‐fold, p = 0.013) and a higher relative retention of muscle mass (1.3‐fold, p = 0.0003) compared with WT. The absence of LAT2 led to increased intramuscular glutamine (Gln) accumulation (6.3‐fold, p < 0.0001), accompanied by a reduction in skeletal muscle proteolysis during fasting (0.61‐fold, p = 0.0004) primarily due to decreased proteasomal and autophagic activity (0.45‐fold, p = 0.016 and 0.7‐fold, p = 0.002, respectively). Ex vivo incubation of LAT2KO muscle with rapamycin recovered proteolysis function, demonstrating a mTORC1‐dependent pathway. Decreased proteolysis in LAT2KO animals was associated with increased mTORC1 translocation to the lysosome (mTORC1‐Lamp1 colocalization in fasted LAT2KO muscles was 1.23‐fold, p < 0.0001). Of the three muscle loss models tested, differences were observed only during ageing. Young LAT2KO mice (3 M) exhibited muscle tone and MurF1 expression levels comparable to those of older WT mice (12 M) (0.44‐fold, p = 0.02 and 0.48‐fold, p = 0.04, respectively). Conclusion LAT2 has a critical role in regulating Gln efflux from skeletal muscle. The absence of LAT2 led to elevated intracellular Gln levels, impairing muscle proteolysis by inducing mTORC1 recruitment to the lysosome. Further, chronic Gln accumulation and decreased proteolysis were found to induce the early onset of an age‐related muscle phenotype.